Identification and Phylogenetic Tree Determination of Spodoptera frugiperda from Java Based on mtDNA COI Sequence Analysis - Ani Widarti; Enie Tauruslina; Idah Faridah; Willing Bagariang; Hadi Suyanto; Didah Mahmudah; Rista Susanti; Rosalia Maryana; Carwika Carwika (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2022)
Molecular confirmation of the existence of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) on Java Island has not been widely reported. This study aimed to identify the armyworm from Java Island molecularly based on DNA mitochondrial cytochrome oxidase I (MtDNA COI). There were six armyworms collected from West Java Province (Cirebon - JWB1, Garut - JWB2), Central Java Province (Wonogiri - JWTH), East Java Province (Gresik - JWTR), DI Yogyakarta Province (Bantul - DIY), and Banten Province (Serang - BNT). The results showed that the fall armyworm originating from Java was verified as Spodoptera frugiperda. There were genetic variations between them, which had species closeness between regions and countries, namely the genetic similarity of S. frugiperda Java and West Sumatra, as well as to China, Korea, and India. S. frugiperda from Central Java (JWTH), Banten (BNT), West Java 1 (JWB1), and Yogyakarta (DIY) has genetic similarity to S. frugiperda from Solok (No. Acc. MW876212.1), West Pasaman (No. Acc. MW876211.1), China (No.Acc. MK591010.1) and Korea (No.Acc. MN427930.1). Meanwhile, S. frugiperda West Java (JWB2) and East Java have genetic similarity to S. frugiperda from India (No. Acc. MT732476.1), Padang Pariaman (No. Acc. MW876208.1), and Tanah Datar (No. Acc. MW87621.0).